Blended Learning as Solution in Character Education during the COVID-19 Pandemic - Masturin, Masturin; Zaman, Wahyu Khoiruz (Pascasarjana IAIN Kudus, 2022)
The learning process during the COVID-19 period has experienced a distortion in the learning quality, which resulted in less-than-optimal learning outcomes. It is because online learning can only convey material in the cognition aspect. Thus, a learning strategy is needed to convey material in the cognition, affection, and psychomotor aspects, one of which is blended learning. For this reason, this study aims to describe and analyze the blended learning model applied during the COVID-19 pandemic. This study used a qualitative approach with a case study design, while the informants were determined by purposive sampling. The data collection techniques employed were in-depth interviews, participant observation, documentation, and focus group discussions. Checking the data validity was carried out by extending the researcher's presence in the field, deepening observations, triangulation, peer discussion, member checking, transferability, dependency, and confirmability. This study’s results revealed that the blended learning model during the COVID-19 period was effective in the learning process because it combined online and face-to-face learning methods. Then, this study suggests that the learning process must be well designed, including during the COVID-19 period, with the hope of making students comfortable and optimal learning outcomes.